2019
DOI: 10.3892/ol.2019.10468
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑EpCAM antibodies for detection of metastatic carcinoma in effusions and peritoneal wash

Abstract: Epithelial cell adhesion molecule (EpCAM) has been used as diagnostic/prognostic marker and therapeutic target. The aim of the present study was to compare immunoreactivity of antibodies against distinct epitopes in the ectodomain of EpCAM for detection of carcinoma from different primary sites and of different histological types in effusions and peritoneal wash. Two antibodies against epitopes in the EGF-like domain I (clones Moc-31 and Ber-EP4) and one antibody against the epitope in the cysteine-poor region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…EMT, and taking into account that carcinomatous cells can lose EpCAM expression due to this process (Hyun et al, 2016), it is possible to explain why some malignant effusions with positive conventional cytology (May-Grünwald-Giemsa staining) and/or PAP-cytology/IHC have negative FC results. It has been suggested that using EpCAM antibodies against different epitopes of the molecule would increase the chance of its detection in metastatic carcinoma effusions (Carneiro et al, 2019). In addition, some poorly differentiated epithelial tumors downregulate the expression of EpCAM (Pillai et al, 2013), potentially leading to contradictory data between FC and cytology.…”
Section: T a B L Ementioning
confidence: 99%
“…EMT, and taking into account that carcinomatous cells can lose EpCAM expression due to this process (Hyun et al, 2016), it is possible to explain why some malignant effusions with positive conventional cytology (May-Grünwald-Giemsa staining) and/or PAP-cytology/IHC have negative FC results. It has been suggested that using EpCAM antibodies against different epitopes of the molecule would increase the chance of its detection in metastatic carcinoma effusions (Carneiro et al, 2019). In addition, some poorly differentiated epithelial tumors downregulate the expression of EpCAM (Pillai et al, 2013), potentially leading to contradictory data between FC and cytology.…”
Section: T a B L Ementioning
confidence: 99%
“…Epithelial cell adhesion molecule (EpCAM) is a transmembrane glycoprotein that is involved in cell adhesion, signaling, migration, proliferation and differentiation [ 21 , 22 ]. More than 90% of metastatic lesions of malignant ovarian tumors, as well as many other carcinomas, overexpress EpCAM relative to normal epithelial cells and normal mesothelium [ 21 , 23 , 24 , 25 ]. Furthermore, EpCAM expression in tumor cells is not confined to the basolateral side as in normal cells, making cancer cells better accessible to EpCAM-targeting agents via the apical side [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunoreactivity of anti-p16 antibody was evaluated and compared with the expression of claudin-4 and MOC-31 by using total immunostaining score (TIS), which is the product of the proportion score and the intensity score. This score has been previously used to evaluate the expression of p16 and EpCAM in histological specimens [9,14,15]. Here, this score was applied to enable comparison between p16 expression with those of MOC-31 (anti-EpCAM clone) and claudin-4.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were freshly prepared and no fixatives or preservative solutions were used. Cell block preparation and immunocytochemistry was performed as previously described [14], using the plasma-thromboplastin method. In brief, samples were centrifuged and 100 μl of plasma and 100 μl of thromboplastin (Stago®, Asnières sur Seine, France) were added onto the cell pellet.…”
Section: Methodsmentioning
confidence: 99%